Efektivitas Edukasi Obat untuk Pasien Diabetes Mellitus pada Masa Pandemi Covid-19 di Puskesmas Kecamatan Cempaka Putih, Jakarta Pusat: The Effectiveness of Medication Guidance for Diabetes Mellitus Patients during the Covid-19 Pandemic at the Cempaka Putih District Primary Health Care, Central Jakarta - Nanda Puspita; Khairunnida Khairunnida (Jurnal Sains dan Kesehatan, 2022)
Diabetes mellitus is a chronic disease requires continuous therapy by professional health workers and self-care management from the patients. To support this, diabetic patient who seek treatment at the primary healthcare facilities is recommended to join The Chronic Disease Management Program (Prolanis). During the Covid-19 pandemic, the frequency of diabetic-related prolanis activities became less monitored, especially regarding the accuracy of using antidiabetic oral (ADO). A quasi-experimental study was conducted through drug education by pharmacists to determine the effect of such education on clinical outcomes, namely the patient's glycosylated hemoglobin (HbA1c) levels. The results showed that there was a decrease in HbA1c levels (1.31%) in the intervention group (n=7) and an increase in HbA1c (0.51%) in the control group (n=17; p=0.078). Eventhough it was not statistically significant due to limited research subjects, education on the proper use of ADO can reduce HbA1c levels in diabetic patients.